Long-term outcomes of initial thoracic endovascular repair versus medical therapy in acute uncomplicated type B aortic dissection: real-world evidence from a nationwide claims database in Japan – a retrospective cohort study - Naohiro Yonemoto; Yuki Kimura; Hiroshi Ohtsu; Nobuyoshi Azuma; Kazuhiro Sase (BMJ Surgery, Interventions, & Health Technologies, 2025)
Objectives To compare the long-term outcomes of initial thoracic endovascular aortic repair (TEVAR) versus initial medical therapy (iMT) in patients with acute uncomplicated type B aortic dissection (uTBAD), using real-world evidence from a nationwide claims database in Japan. This study aligns with stage 4 of the Idea, Development, Exploration, Assessment, and Long-term Study (IDEAL) framework for surgical innovation.Design A retrospective cohort study using propensity score matching (PSM) to balance baseline characteristics.Setting Japanese nationwide health insurance claims database, between 1 January 2015 and 31 December 2023.Participants Among 40 229 cases with tentative codes for aortic dissection (International Classification of Diseases-10: I71.0), 4995 met all eligibility criteria for acute uTBAD. Among these patients, 96 underwent TEVAR in the subacute phase (15–90 days post diagnosis), while 4899 were managed with iMT. After PSM, 96 TEVAR cases were matched to 480 iMT cases in a 1:5 ratio.Main outcome measures The primary outcomes were aorta-related events and all-cause mortality. The secondary outcome was the frequency of follow-up CT imaging every year.Results After PSM, the baseline characteristics of both groups were balanced. Median age was 56 years (IQR: 50–62 years) in both groups, and follow-up duration was similar (TEVAR: 31 months; iMT: 28 months, p=0.84).At 60 months, Kaplan-Meier estimates showed an aorta-related event rate of 21.9% (95% CI: 12.6% to 36.4%) for TEVAR and 19.9% (95% CI: 15.6% to 25.2%) for iMT (p=0.99).All-cause mortality was 4.4% (95% CI: 1.4% to 13.6%) for TEVAR and 6.6% (95% CI: 4.0% to 10.6%) for iMT (p=0.70). No significant differences were observed.Conclusions While aorta-related events accumulated steadily in the crude iMT group, no survival benefit was observed for subacute TEVAR. These findings support ongoing randomized controlled trials and show the utility of claims-based analyses in IDEAL Stage 4.